ANALISIS PENINGKATAN KUALITAS SUMBER DAYA PENDIDIKAN DI SEKOLAH TINGGI ILMU ADMINISTRASI NUSANTARA SAKTI SUNGAI PENUH: ARDIANTO ARSAN, S.Sos., M.Si - Ardianto Arsan (LPPM STIA Nusantara Sakti, 2018)
Increased Quality of Education Resources in High School of Administrative Sciences Nusantara Sakti Sungai Penuh. The purpose of this study was to determine the Improvement of the Quality of Educational Resources in Nusantara Sakti Sungai Penuh College of Administrative Sciences. The research approach used in this study is qualitative. The techniques and data collection in this study were interviews and documentation, data collection tools in the form of questionnaires, pens, books / papers. This research informants numbered 7 people. The results of this study indicate that improving the quality of educational resources in high schools is very important in improving quality education. To produce quality graduates in accordance with the expectations and needs of the community and the students themselves, have faith and be devoted to the almighty and achiever god, to live a democratic life, to become the next generation of the nation in building quality universities. It can be concluded that the improvement of the quality of educational resources in the administrative high school of the archipelago of Sakti Sungai Penuh has carried out its role and task well seen by the current Accreditation B.